Hasil Belajar Siswa Dalam Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VII Ditinjau Dari Metode Snowball Throwing Dan Think Talk Write Di SMP 2 Muhammadiyah Karanganyar Tahun Ajaran 2015 / 2016 - Antasi, Reny, Drs. Djumali, M. Pd (2016)
This study aims to examine whether there are differences between the use of learning outcomes IPS Throwing Snowball method by method write and talk think whether learning outcomes through the use of IPS subjects Throwing Snowball method is better than the use of methods of talk think write. The subjects in this study were students of class VII SMP Muhammadiyah Karanganyar 2 Academic Year 2015/2016. A Class VII consists of 24 students as the control class treated Snowball Throwing learning methods and class VII B consists of 24 students as the experimental class were treated with the method of talk think write. Methods of data collection is done through tests and documentation. To test instrument using validity and reliability of the test. Techniques of data analysis prerequisite test using test of normality and homogeneity. Data analysis techniques to test this hypothesis using t-test. The results showed differences in social studies learning outcomes among students who learn using Snowball Throwing with students who learn using talk think write. It can be seen from the average value of class VII A as a control class that uses learning strategies snowball throwing is 71.42. While the average value of class VII B as a class experiment using talk think write is 75.50. The study concluded that there are differences in learning outcomes social studies class VII using talk think write better than using Snowball Throwing.